The Alphabetical Reference Dictionary: Between Scientific Methodology and Critical Perspective - Zahid Murtaza; Prof. Dr. Muhammad Abuzarr Khalil; Saadia Hijab Zahra (Journal of Religion and Society, 2025)
This research presents an in-depth analytical and critical study of al-Muʿjam al-Marjaʿ al-Abjadi (The Alphabetical Reference Dictionary), aiming to evaluate its scholarly merit within the broader framework of modern Arabic lexicography. The study is structured into three main sections, each addressing a distinct yet interconnected dimension of the dictionary. The first section provides a descriptive overview, introducing the dictionary’s historical and linguistic context, its stated objectives, target readership, and the scope of its lexical coverage. It highlights the importance of alphabetical arrangement in facilitating accessibility for both native speakers and learners of Arabic, as well as its role in bridging Arabic and English linguistic resources.The second section delves into the author’s methodology, examining the principles governing lexical selection, the ordering of entries, the precision and clarity of definitions, and the inclusion of illustrative examples. Special attention is given to the balance between comprehensiveness and conciseness, as well as the linguistic accuracy and user-friendly format adopted by the compiler. The third section offers a critical evaluation, identifying the dictionary’s notable strengths such as ease of navigation, linguistic precision, and practical relevance while also addressing its limitations, including insufficient semantic depth in certain entries, lack of thematic categorization, and limited cross-referencing. By integrating descriptive, methodological, and critical perspectives, this study not only assesses the dictionary’s contribution to bilingual lexicography but also situates it within contemporary debates on lexicographical standards. Ultimately, the research underscores the need for ongoing refinement in dictionary compilation to meet the evolving demands of both academic and general users. Keywords: Alphabetical, Reference Dictionary, Scientific Methodology, Critical Perspective